2020
DOI: 10.1177/2158244020961118
|View full text |Cite
|
Sign up to set email alerts
|

Determinative Variables Toward Promoting Use of Active Modes of Transportation: Enhancing Level of Sustainable Mobility in Communities

Abstract: Most current transportation systems around the world are cause for pressing concern and a menace to sustainability of social justice, and economic and environmental vitality. From a universal agreement that transportation needs an urgent alteration in travel modes, policies, planning, and behaviors through to the emergence of sustainability in the transportation sector, a significant and central vision has emerged to guide urban policymakers, transportation planners, and public health officials. During the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
(167 reference statements)
0
1
0
1
Order By: Relevance
“…Using the following search criteria in the Web of Science database (search date: 4 July 2021), 31 review papers were found: title: ("sustainable mobility") or title: ("sustainable transport"); languages: (English); document types: (review); timespan: all years; and indexes: SCI-EXPANDED, SSCI, A&HCI, ESCI. However, of these 31, 5 are closely related to a general view of sustainable mobility or transport [7][8][9][10][11].…”
Section: Previous Focus Of Reviews On Sustainable Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Using the following search criteria in the Web of Science database (search date: 4 July 2021), 31 review papers were found: title: ("sustainable mobility") or title: ("sustainable transport"); languages: (English); document types: (review); timespan: all years; and indexes: SCI-EXPANDED, SSCI, A&HCI, ESCI. However, of these 31, 5 are closely related to a general view of sustainable mobility or transport [7][8][9][10][11].…”
Section: Previous Focus Of Reviews On Sustainable Mobilitymentioning
confidence: 99%
“…Dehghanmongabadi & Hoşkara [8] aims to point out critical determinative variables to promote active transportation modes and consequently contribute to sustainable mobility in communities. Using as key search terms "sustainable transportation", "sustainable mobility", and "active transportation", this review searched journal articles (SCI and SSCI), books, published conference papers, reports, and published research works.…”
Section: Previous Focus Of Reviews On Sustainable Mobilitymentioning
confidence: 99%
“…Al respecto hay algunos indicios que exploran esta conexión, sin embargo, como se verá más adelante, es todavía una cuestión muy periférica. 6 Los estudios con los que se cuenta arrojan que la movilidad de las mujeres -en términos generales-es más sostenible, pues sus trayectos generan menos emisiones: viajan menos, recorren distancias más cortas, hacen menor uso del automóvil, suelen utilizar en mayor medida el transporte público y los recorridos peatonales son mayores, además de manifestar mayor interés en cambiar los impactos negativos del transporte motorizado (Hanson, 2010;Uteng, 2012;Peters, 2013;Dehghanmongabadi y Hoşkara, 2020;González-Sánchez et al, 2021). A partir de lo anterior se podría deducir que las mujeres sostienen conductas más sostenibles en el campo de la movilidad, o al menos suponer que ellas tienen mayor capacidad de adaptación a cambios promovidos por intervenciones en dicha dirección.…”
Section: Género Y Movilidad Sostenibleunclassified
“…In the transport domain, accessibility is considered as an extremely valuable indicator to exert a positive influence on using public transport ( Moniruzzaman and Paez, 2012 ; Cavallaro and Dianin, 2020 ). A generally accepted definition of accessibility is the potential opportunity for interaction ( Hansen, 1959 ), which means the ease of reaching a destination by a particular travel mode ( Dehghanmongabadi and Hoşkara, 2020 ). Although the concept of accessibility is easy to understand, it is limited in capturing personal subjective feelings of the same accessibility ( Curl et al, 2015 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%